Designing Tool for Supporting the Heart Contraction Process - Duong, Trong Luong; Nguyen, Thai Ha (Old Journal, 2020)
Currently, the number of people with heart failure is increasing (1-2% of the world’s population). This is an alarming problem and a topical topic. Besides, the cost for each treatment of heart failure inpatients is about VND25 million – a relatively high cost for many families in Vietnam. Recently, there are several types of devices support heart failure patients have been manufactured and commercialized. However, these devices are imported and very expensive, from VND900 million or more, and not including the cost of transplantation, treatment, and medication. Therefore, researching and designing a tool for supporting the contractility of the heart is essential. This paper presents the research and design of a tool for supporting the contractility of the heart. The results of this study were tested on a fake heart made by silicon material.